Exploring Servant Leadership and Intrapreneurship with Organizational Antecedents in Indonesian Schools - Sanjaya, Regi; Marianti, Maria Merry; Sulungbudi, Brigita Meylianti; Kiboy, Alexander Chou (Pandawan, 2024)
The applicability of the servant leadership concept is still growing, and researchers are currently exploring model development. On the other hand, since organizations need to innovate in order to adapt proactively to change and ensure sustainability, intrapreneurship becomes particularly important for the development of any organization, whether it is a business or a non-profit. Numerous studies have indicated that servant leadership can stimulate creative and innovative behaviors, which are essential aspects of intrapreneurship. However, the existing literature on servant leadership primarily focuses on leader characteristics, with limited knowledge about other influencing factors. This research uniquely explores organizational antecedents, addressing gaps in how servant leadership fosters intrapreneurship. This study aims to explore and identify the antecedents of servant leadership beyond individual characteristics. Participants in this study include principals from various Indonesian private schools. We conducted thorough interviews to gather data, and the transcripts from these interviews were meticulously analyzed to identify key themes. The interview data were analyzed using thematic coding, wherein recurring patterns and themes were identified through a systematic, iterative process. The analysis followed a six-phase framework for thematic analysis, starting with familiarization with the data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and finally producing the report. According to the results, potential variables for future research in servant leadership and intrapreneurship models include organizational vision and mission, satisfaction with compensation, serving culture, and the role model of the manager.